Neuromuscular, retinal, and reproductive impact of low-dose polystyrene microplastics on Drosophila. (1st January 2022) - Liu, Hsin-Ping; Cheng, Jack; Chen, Mei-Ying; Chuang, Tsai-Ni; Dong, Jhou-Ciang; Liu, Chuan-Hsiu; Lin, Wei-Yong
Abstract: Facing the challenge of global microplastics (MPs) pollution, full characterization of MPs biohazards is urgent. Recent intensive studies revealed that the toxicity depends on the material, size, and exposure concentration of MP. To better elucidate MPs biohazards, we investigated the impact of polystyrene-MPs of size 0.1 μm at a low dose of 50 μg/L on the neuromuscular, retinal, and reproductive phenotypes of fruit fly model, by voltage-clamped electrophysiology, electroretinogram, and reproductive assay, respectively. We found that MPs decreased the frequency of spontaneous junction currents of synapse and altered the receptor potential amplitude of the retina. Furthermore, MPs lowered the rate of embryo-laying of fruit flies. The differential gene expression of ligand-receptor interaction, endocytosis, phototransduction, and Toll/Imd signaling pathways might underlie these MPs-induced phenotypes. These findings call for further investigation on the potential biohazards of low-dose MPs. Graphical abstract: Image 1 Highlights: Low-dose PS-MP shows biological hazards in the fruit fly model. MP interferes with mEJC frequency of synapse. MP alters retinal receptor voltage difference. MP lowers the rate of embryo laying. Differential gene expression in related pathways was observed.